Faktor Remaja Yang Terjebak Dalam Permainan Judi Online : (Studi Kasus Pada Generasi Milenial Di Jakarta) - Muhammad Ragil Mahendra; Ratih Damayanti (Shofanah Media Berkah, 2024)
The phenomenon of online gambling is increasingly becoming a serious concern among society, especially among teenagers. Wide access to information technology, such as smartphones connected to the internet, makes it easy for teenagers to engage in online gambling. In contrast to conventional gambling, online gambling offers anonymity, easy access, and various types of interesting games. The characteristics of adolescence, which tend to be full of exploration, search for identity, and a tendency to take risks, make this age group vulnerable to environmental influences and the temptation of online gambling. Individual factors such as curiosity, economic pressure, and the need for entertainment are the main causes of teenage involvement. Additionally, aggressive promotions from digital gambling platforms often attract their attention. The impacts include financial problems, mental health problems, and potential future destruction. This research aims to analyze the factors that cause teenage involvement in online gambling, examine its impact, and formulate effective preventive solutions. It is hoped that this research can make a real contribution to efforts to prevent online gambling among teenagers through education, policy and community participation approaches.